(untitled) - Brynie, Faith Hickman (Hoboken, NJ, 2005)
When the science project is due, this book comes to the rescue. With the trend toward hands-on learning, millions of elementary students have to do science projects. Typically, they mention this to their parents the night before the project is due. This book helps busy parents help their children create last-minute science projects using materials commonly found around the house. It features chapter breakouts grouped by science project subject, two-page spreads devoted to specific science projects, and factoids to get kids interested in the subject. Parents can quickly pick an appropriate project and spur their future scientists toward success! Faith Hickman Brynie (Bigfork, MT) is a writer specializing in science and health; she holds a PhD in science education, curriculum, and instruction and is a frequent writer for the children’s science magazine Odyssey, as well as the editor of various elementary school science textbooks.
Keywords: Science projects,Science,Dự án khoa học,Khoa học; Study and teaching (Elementary),Nghiên cứu và giảng dạy (Tiểu học)